DSS in numbers - Filip, Florin Gheorghe; Suduc, Ana-Maria; Bîzoi, Mihai (Technological and Economic Development of Economy, 2014)
Decision Support Systems (DSS) have evolved in time, influenced by technological and organizational developments. The scientists’ interest for DSS has increased over the years and the use of this type of systems has spread in all domains of activity. The paper presents the results of a literature search, made in September 2013, regarding the Decision Support Systems evolution as it is reflected in three scientific databases (ScienceDirect, IEEE Xplore Digital Library and ACM Digital Library). The aim of this research is to present the evolution in time of the published DSS research materials and to test the usefulness and relevance, for the topic searched, of the information provided by the above mentioned databases.